Security Communities and their Neighbours - Bellamy, A. author. aut Link
X, 221 p.
Keywords: Does the proliferation of security communities around the world presage a new era of competition between regions or an era of intensified global integration? This important new study assesses the relationship between security communities and their neighbours and asks whether processes of regional integration will contribute to a global 'clash of civilizations'. Drawing on four detailed case studies (Western Europe, Southeast Asia, the Persian Gulf and North America), Alex J. Bellamy argues that the more mature a security community becomes, the less likely it is to become a 'regional fortress'.